Evaluation of accuracy, integrity and availability of ARNS multi-constellation signals for aviation users in Australia - Deo, Manoj; El-Mowafy, Ahmed (2017)
Aviation requires the use of signals operating in the protected aeronautical radionavigation service (ARNS) band. For GPS, only single frequency signal (L1 C/A) are currently allowed, which contains ionosphere delays. Although Space Based Augmentation Systems (SBAS) may be used to enhance the accuracy and integrity of single frequency aviation users, this service is not available in Australia. GPS Block IIF satellites transmitting the L5 civil signal, which falls in the ARNS band allows for elimination of ionospheric delay when combined with L1 C/A. Beidou has two ARNS protected signals, whereas Galileo has three protected signals. With these systems, multi-frequency multi-constellation (MFMC) GNSS may become a primary means of navigation in the next decade for all phases of flight operations, including precision approach. This paper presents the current status of the accuracy, integrity and availability of ARNS protected signals in Australia which will help in early understanding of its future performance. The present number of MFMC satellites in operation can facilitate this initial testing. MFMC data for ARNS signals collected from several Australian sites was analysed to demonstrate the current snapshot of accuracy, availability and integrity for aviation. Promising results are shown and further improvements are expected as additional satellites are launched, with improved information. Analysis of integrity monitoring with tested MFMC data showed that integrity can be achieved for almost 100% of the time.